Edukasi Pentingnya Mengenal Stunting Secara Dini Sebagai Preventif Terjadinya Stunting pada Kelompok Ibu di Perumahan Binawidya, Tampan, Pekanbaru (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2024)
Stunting is a condition of malnutrition that occurs in toddlers that can be associated with inadequate nutrition for a long time and repeatedly.  Many cases of stunting occur in children under five. The fulfilment of adequate nutrition in toddlers both macro and micro nutrients is needed to minimise the occurrence of stunting. The role of parental knowledge, especially a mother, is very important in identifying symptoms of stunting early and fulfilling the nutritional needs of toddlers to prevent stunting in family members.  By knowing the symptoms of stunting early, parents can anticipate the impact of stunting, while maternal knowledge about fulfilling toddler nutrition can prevent stunting in children.The partner in this PKM activity is a group of mothers in RT 02 RW 06 BinaWidya Housing, Tampan. The average mother in Bina Widya Housing has children under five and many do not know about stunting or management of stunting prevention management. This Community Service activity aims to increase mothers' knowledge about stunting.  This PKM method uses lectures on stunting which include understanding stunting, causes, how to recognise the symptoms of stunting early and prevention of stunting.  The results of PKM activities show an increase in mothers' knowledge about stunting
Keywords: edukasi; stunting; ibu